Historical dictionary of science fiction in literature - Booker, M. Keith (Lanham : Rowman & Littlefield, 2015)
"The Historical Dictionary of Science Fiction in Literature covers the history of Science Fiction in literature through a chronology, an introductory essay, and an extensive bibliography. The dictionary section has over 300 cross-referenced entries significant people, themes, critical issues, and the most significant genres that have formed Science Fiction literature. This book is an excellent access point for students, researchers, and anyone wanting to know more about this subject" --
Includes bibliographical references (pages 355-396).
Editor's foreword / Jon Woronoff -- Preface -- Acronyms and abbreviations -- Reader's note -- Chronology -- Introduction -- The dictionary -- Bibliography -- About the author.
Keywords: Science fiction -- Dictionaries; Science fiction -- History and criticism -- Handbooks, manuals, etc